The mediation role of top management support in the adoption of cloud computing in Malaysian SMEs - Ho, Jo Ann; Subramaniam, Anusuiya; Teh, Raymond; Kamal Basha, Norazlyn (Inderscience Publishers, 2024)
With only 3.63% of total IT spending on cloud computing and a growth rate of 13.13%, Malaysia's adoption of cloud computing is lower than others. The purpose of this study is to find out the mediation role of top management support together with the DOI's innovative characteristics and TOE's contexts on cloud computing adoption among Malaysian SMEs. This study was able to determine the relationships between IV and DV in a more accurate way and the findings are crucial to understanding how to drive a higher cloud computing adoption rate among Malaysian SMEs with top management support as the mediator, which eventually can drive better firm performance. An empirical cross-sectional research paper that was conducted on Malaysian SMEs with 352 participants was carried out with a quantitative online survey with a five-point Likert scale and systematic sampling technique to collect the primary data. It was concluded and proven that top management support has a significant mediating effect on cloud computing adoption and DOI's innovative characteristics and TOE's contexts have positive influences on the adoption of cloud computing.